2020
DOI: 10.1111/jipb.12986
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene promotes seed iron storage duringArabidopsisseed maturation via ERF95 transcription factor

Abstract: Because Iron (Fe) is an essential element, Fe storage in plant seeds is necessary for seedling establishment following germination. However, the mechanisms controlling seed Fe storage during seed development remain largely unknown. Here we reveal that an ERF95 transcription factor regulatesArabidopsisseed Fe accumulation. We show that expression ofERF95increases during seed maturation, and that lack of ERF95 reduces seed Fe accumulation, consequently increasing sensitivity to Fe deficiency during seedling esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…In of the iron deficiency responses in these two apple species (Liu et al, 2018;Zhang et al, 2020a). In contrast, ERF95 was recently proposed to promote iron storage in Arabidopsis seeds (Sun et al, 2020). However, how iron distribution is controlled in seeds is not clearly established even if it was recently proposed that B3 TFs, which are involved in the regulation of embryo development and seed maturation, might be good candidates (Roschzttardtz et al, 2020).…”
Section: The Transcriptional Regulation Of Iron Homeostasis Is Not Restricted To the Activity Of Bhlh Tfsmentioning
confidence: 99%
“…In of the iron deficiency responses in these two apple species (Liu et al, 2018;Zhang et al, 2020a). In contrast, ERF95 was recently proposed to promote iron storage in Arabidopsis seeds (Sun et al, 2020). However, how iron distribution is controlled in seeds is not clearly established even if it was recently proposed that B3 TFs, which are involved in the regulation of embryo development and seed maturation, might be good candidates (Roschzttardtz et al, 2020).…”
Section: The Transcriptional Regulation Of Iron Homeostasis Is Not Restricted To the Activity Of Bhlh Tfsmentioning
confidence: 99%
“…In harsh conditions such as high salt levels, extreme drought and high concentrations of heavy metals or arsenic, halophytes [ 23 , 24 ], xerophytes [ 25 , 26 ] and arsenic hyperaccumulators [ 27 , 28 ] have formed their own unique morphology that resists abiotic stress during long-term evolution. Plant responses to abiotic stresses involve a large number of transcription factors [ 29 , 30 , 31 , 32 ]. Results from genome-wide sequencing, differential transcriptome analysis, and functional analysis of numerous genes have shown that the transcription factor families involved in abiotic stress tolerance in plants include bHLH (basic helix-loop-helix) [ 33 , 34 , 35 ], WRKY [ 10 , 36 , 37 , 38 ], bZIP (basic leucine zipper) [ 39 , 40 , 41 ], homeodomain [ 42 , 43 ], HSF [ 3 , 44 , 45 , 46 ], NAC [ 47 , 48 , 49 ], MYB [ 50 , 51 , 52 ], MADS-box [ 53 , 54 , 55 ], AP2/ERF [ 56 , 57 , 58 ], and zinc-finger proteins [ 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional work detected no evident Fe influx and only a slight increase in Fe content during the embryogenesis stage, while in the following maturation phase there is a huge increase in Fe influx that reaches a maximum before onset of the desiccation stage (Ravet et al, 2009). In line with these findings, a recent study revealed that ethylene is important for the control of embryonic Fe accumulation during seed maturation through the mediation of an ERF95 transcription factor (Sun et al, 2020). These observations indicate that inflow of Fe into seeds is under strict control, especially during early seed development.…”
Section: Discussionmentioning
confidence: 65%
“…ChIP assay was performed as described previously with the following modifications (Sun et al, 2020). In brief, the early developing siliques of Col-0 and Flag-INO-ox transgenic lines were collected and fixed with 3% formaldehyde under vacuum for 10 min.…”
Section: Chip-qpcr Assaymentioning
confidence: 99%